Evaluation of blackbody radiation shift with 2 × 10−18 uncertainty at room temperature for a transportable 40Ca+ optical clock. (1st April 2021) - Zhang, Ping; Cao, Jian; Yuan, Jin-bo; Liu, Dao-xin; Yuan, Yi; Wei, Yuan-fei; Shu, Hua-lin; Huang, Xue-ren
Abstract: Blackbody radiation (BBR) temperature and its uncertainty mainly contribute to the BBR shift uncertainty, which is one of the challenges in most ion optical clocks. Here, an improved BBR temperature evaluation method based on the analysis of the effective solid angle of an ion trapping system using the finite element method is presented. To effectively suppress the BBR temperature uncertainty, the structure of an ion trap was optimized to reduce the effective solid angle of the insulating supports, and a BBR shield was employed to reduce the influence of the surrounding BBR in the newly developed ion trap system. Due to radiofrequency field, it is difficult to evaluate the temperature of BBR shield accurately using contact-temperature-sensors inside the vacuum chamber. We used a well shielded platinum resistance temperature sensor to measure the temperature of the shield from the outside of the vacuum chamber. Through a detailed evaluation, the BBR temperature uncertainty of this newly designed system is 0.17 K, corresponding to a BBR frequency shift uncertainty of 2 × 10 −18 for the 40 Ca + optical clock. This improvement of the BBR temperature uncertainty using the active adjustment of the distribution of the effective solid angle of the ion trapping system, without a complicated cryogenic trap, is very suitable for transportable optical clocks operating at room temperature (∼295 K).